Connective tissue abnormalities in MRL/1 mice. Issue 6 (June 1986) - Edwards, J C; Cooke, A; Moore, A R; Collins, C; Hay, F; Willoughby, D A
Abstract : Pathological changes in the connective tissue of the limbs of MRL/1 mice are described. Focal infiltrates of polymorphs or large mononuclear cells, or both, were seen both in synovial lining and subcutaneous tissue. Infiltrates were associated with vasculitis in some cases. Deposits of amorphous material were seen in and around joints and in foot pads. The material was more particulate and refractile than typical 'fibrinoid' and showed a positive Feulgen reaction. It was not surrounded by palisading cells and when seen in synovial tissue was not usually associated with changes in synovial lining cells. No obvious difference was seen between intra-articular and extra-articular lesions. Lesions in subcutaneous tissue occurred exclusively in the foot pads. Lymphocyte infiltration was not prominent at any site and no follicle formation was seen. Of two colonies studied, only one showed a significant increase in lining cell numbers in synovial tissue. Exercised animals had a similar distribution and severity of disease to those of matched controls. All lesions described were distinguishable from non-specific inflammatory lesions in normal control mice and MRL/++ mice on assessment of unmarked sections. The relation between these connective tissue lesions and the changes found in human chronic synovitis is discussed.